The effectiveness of local coastal plant Spirulina cultivated to reduce anemia in pregnant women - Risnawati, Risnawati; Herman, Herman; Jumatrin, Nur Fitriah; Fitra, Wa Ode; Supriadi, Supriadi (Universitas 'Aisyiyah Yogyakarta, 2025)
Anemia is one of the common health complications in pregnant women and is a health problem of global concern. Anemia during pregnancy has an impact on maternal and fetal health problems and contributes to increased maternal and fetal mortality and morbidity. Spirulina (Arthrospira platensis) is a marine plant that is rich in nutrients such as protein, amino acids, vitamins, minerals, carbohydrates, iron, sodium, potassium, calcium, magnesium, lead, cadmium, arsenic, and phosphorus. Spirulina plants processed in the form of supplements can prevent and overcome health problems such as anemia. The purpose of this study was to determine the effectiveness of local coastal plants Spirulina (Arthrospira platensis) in the form of supplements in overcoming anemia in pregnant women. The research method used was a quasi-experimental with a pre-post test design. The study population was pregnant women. The number of samples was 15 people, with a purposive sampling technique. The intervention carried out was the administration of spirulina capsules at a dose of 800 mg/day for 21 days. Data analysis using the Paited T test. The results showed that spirulina supplementation significantly (p value = 0.00 <α value = 0.05) increased Hb levels in pregnant women suffering from anemia in the coastal area of ​​Konawe Regency. Increasing the dose with a shorter duration is expected to be able to overcome the problem of anemia efficiently.